Characterization of the formation of somatic embryos from mature zygotic embryos of Passiflora ligularis Juss. - Oliveira Prudente, D. de; Paiva, R.; Carpentier, Sebastien C.; Swennen, Rony L.; Nery, F.C.; Silva, L.C.; Panis, Bartholomeus (Springer, 2017)
Passiflora ligularis Juss. is an endemic species from South America with important medicinal and economical properties. The development of improved micropropagation techniques is necessary to provide rapid and efficient clonal propagation of elite genotypes with high resistance and uniform production, as well as a system that can be used for genetic transformation. For this reason, we focused on establishing a protocol for somatic embryogenesis in P. ligularis from mature zygotic embryos. Our results demonstrate that the highest frequencies of somatic embryo formation was observed on a culture medium supplemented with 27.2 µM 2,4-diclorophenoxyacetic acid plus 4.5 µM 6-benzyladenine. Histological analyses of somatic embryogenesis were performed every 7 days after induction over 60 days of exposure to the medium. We present clear evidence for the precise origin of de-differentiation. Initial cell divisions occurred from a group of cells (multicellular origin) on the abaxial surface of the cotyledon in the periphery of the epidermal tissues of mature zygotic embryos after 14 days of incubation. After 21 days, internal segmenting divisions resulted in the embryogenic character of the tissue. Globular embryos contain a protoderm surrounding a mass of vacuolated parenchymatous cells and meristematic regions with an observable procambium zone after 45 days. The complete independence of somatic embryos from the adjacent tissues was histologically confirmed by the absence of vascular continuity between them, after 60 days. We describe for the first time the development of somatic embryos in P. ligularis and demonstrate that somatic embryos develop into plants that can later on be acclimatized.